2013
DOI: 10.4236/ajps.2013.45a008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Regulators on Biomass and the Production of Secondary Metabolites in Peppermint (<i>Mentha pi-perita</i>) Micropropagated <i>in Vitro</i>

Abstract: The effects of plant growth regulators on peppermint (Mentha piperita) cultured in vitro were studied for the purpose of maximizing growth and essential oil production in micropropagated plants. The basal medium was experimentally supplemented with the auxin 4-indol-3-ylbutyric acid (IBA) and the cytokinin 6-benzylaminopurine (BAP) individually and in combination. Supplementation with BAP alone resulted in the highest values for root length, root dry weight, shoot length, and numbers of nodes, leaves, and rami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…The use of cytokinin in the cultivation in vitro of peppermint (Mentha piperita) increased the number of nodes, branches and leaves (although a reduced shoot fresh matter) and improved the performance of essential oil extraction, per fresh mass unit. It was also observed that these plants had much longer roots and with higher dry weight than those of control plants (Santoro et al, 2013).…”
Section: Resultsmentioning
confidence: 82%
“…The use of cytokinin in the cultivation in vitro of peppermint (Mentha piperita) increased the number of nodes, branches and leaves (although a reduced shoot fresh matter) and improved the performance of essential oil extraction, per fresh mass unit. It was also observed that these plants had much longer roots and with higher dry weight than those of control plants (Santoro et al, 2013).…”
Section: Resultsmentioning
confidence: 82%
“…(2007) over Salvia officinalis, S. albicaulis and S. dolomitica plants on different stages of aseptic culture demonstrated the presence of shield-shaped glandular scales that produced high quality essential oils. Glandular trichomes were also described on leaf surface in Mentha piperita regenerants (Santoro et al, 2013). Glandular hairs are formed from epidermal outgrowths that divide asymmetrically to produce basal cells (Turner et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Micropropagation is appropriate for species that cannot be efficiently propagated by conventional horticultural techniques and an important tool to select, multiply, and conserve the critical genotypes of medicinal plants in particular (Debnath et al, 2006;Tripathi and Tripathi, 2003). Various medicinal plants and plants of Lamiaceae family in particular have been cloned through micropropagation protocols (Aicha et al, 2013;Chaturvedi et al, 2007;Debnath et al, 2006;Gonc xalves and Romano, 2013;Santoro et al, 2013;Shtereva et al, 2015;Zuzarte et al, 2010). Moreover, germination of seeds in some species, which show low or no germination using conventional techniques, due to dormancy or specific germination requirements, could be greatly increased using in vitro methods (Fay, 1994).…”
Section: )mentioning
confidence: 99%
“…Moreover, BA promoted shoot multiplication in several Lavandula sp. (Gonc xalves and Romano, 2013;Zuzarte et al, 2010), while 6-benzyl-aminopurine (BAP) was used in micropropagation of Mentha piperita (Santoro et al, 2013). In T. fruticans, BAP and kinetin induced similar shoot proliferation (Frabetti et al, 2009); while in T. polium, kinetin gave higher shoot production than BA (Al-Qudah et al, 2011).…”
Section: Pretreatmentmentioning
confidence: 99%